2003
DOI: 10.1191/1352458503ms940oa
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of MS: a comparison of three different clinical settings

Abstract: In order to compare a newly established diagnostic clinic with two existing clinical settings in the management of the diagnostic phase of multiple sclerosis (MS), a retrospective audit was performed over a 12-month period comparing the length of time, adherence to recently published standards and price charged in diagnosing MS in three different clinical diagnostic settings operating within the same hospital: a specifically designed demyelinating disease diagnostic clinic (DDC), a general neurology clinic (GN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Applying the inclusion criteria, 30 articles were included, whereas only three were from the database for mental health, PsycINFO. During the analyses, five categories evolved defining potential areas expected to be affected by the quality of referral information (with reference to the included papers in square brackets): timeliness and delay [3133], attendance/drop-out [3437], unnecessary consultations and investigations [32, 38–42], appropriateness of the referral [32, 43–53] and correctness of prioritisation of patients [36, 40, 44, 5460]. Fifteen preliminary indicators were derived from the abstract of these five categories.…”
Section: Resultsmentioning
confidence: 99%
“…Applying the inclusion criteria, 30 articles were included, whereas only three were from the database for mental health, PsycINFO. During the analyses, five categories evolved defining potential areas expected to be affected by the quality of referral information (with reference to the included papers in square brackets): timeliness and delay [3133], attendance/drop-out [3437], unnecessary consultations and investigations [32, 38–42], appropriateness of the referral [32, 43–53] and correctness of prioritisation of patients [36, 40, 44, 5460]. Fifteen preliminary indicators were derived from the abstract of these five categories.…”
Section: Resultsmentioning
confidence: 99%
“…As well, our study supported the finding that specifically designed demyelinating disease diagnostic clinic offers a better service than other existing models. [5] …”
Section: Discussionmentioning
confidence: 99%
“…Thus, a final accurate outpatient diagnosis of MS requires a number of investigative steps which must, by their nature, take time. The UK National Institute for Health and Clinical Excellence (NICE) guidelines recommend a timeline of 12 weeks from a patient's first referral to a diagnosis of MS, 3 and suggested that it should be no longer than 6 weeks from referral to being seen by a neurologist, and a further 6 weeks until any necessary investigations are completed.…”
Section: Introductionmentioning
confidence: 99%